Bile Acid Network and Vascular Calcification-Associated Diseases: Unraveling the Intricate Connections and Therapeutic Potential - Wang C; Ma Q; Yu X (Clinical Interventions in Aging, 2023)
Cui Wang,1,* Qing Ma,2,* Xijie Yu1 1Laboratory of Endocrinology & Metabolism/Department of Endocrinology & Metabolism, Rare Disease Center, West China Hospital, Sichuan University, Chengdu, Sichuan Province, 610041, People’s Republic of China; 2General Practice Ward/International Medical Center Ward, General Practice Medical Center, West China Hospital, Sichuan University/West China School of Nursing, Sichuan University, Chengdu, Sichuan Province, 610041, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xijie Yu, Department of Endocrinology and Metabolism, Laboratory of Endocrinology and Metabolism, Rare Disease Center, West China Hospital, Sichuan University, No. 37 Guoxue Alley, Wuhou District, Chengdu, Sichuan Province, 610041, People’s Republic of China, Tel +86 2885422362, Fax +86 2885423459, Email xijieyu@hotmail.comAbstract: Bile acids play a crucial role in promoting intestinal nutrient absorption and biliary cholesterol excretion, thereby protecting the liver from cholesterol accumulation and bile acid toxicity. Additionally, bile acids can bind to specific nuclear and membrane receptors to regulate energy expenditure and specific functions of particular tissues. Vascular calcification refers to the pathological process of calcium-phosphate deposition in blood vessel walls, which serves as an independent predictor for cardiovascular adverse events. In addition to aging, this pathological change is associated with aging-related diseases such as atherosclerosis, hypertension, chronic kidney disease, diabetes mellitus, and osteoporosis. Emerging evidence suggests a close association between the bile acid network and these aforementioned vascular calcification-associated conditions. Several bile acids have been proven to participate in calcium-phosphate metabolism, affecting the transdifferentiation of vascular smooth muscle cells and thus influencing vascular calcification. Targeting the bile acid network shows potential for ameliorating these diseases and their concomitant vascular calcification by regulating pathways such as energy metabolism, inflammatory response, oxidative stress, and cell differentiation. Here, we present a summary of the metabolism and functions of the bile acid network and aim to provide insights into the current research on the profound connections between the bile acid network and these vascular calcification-associated diseases, as well as the therapeutic potential.Keywords: bile acid, vascular calcification, aging, farnesoid X receptor, FXR, the G protein-coupled membrane receptor, TGR5